2018
DOI: 10.1186/s12967-018-1646-9
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of potential novel biomarker for diagnosis of complicated Plasmodium vivax malaria

Abstract: BackgroundIn the recent years Plasmodium vivax has been reported to cause severe infections associated with mortality. Clinical evaluation has limited accuracy for the early identification of the patients progressing towards the fatal condition. Researchers have tried to identify the serum and the plasma-based indicators of the severe malaria. Discovery of MicroRNA (miRNA) has opened up an era of identification of early biomarkers for various infectious and non-infectious diseases. MicroRNAs (miRNA) are the sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…Still, some issues remain, including the lack of a standardized protocol regarding specimen collection, handling, and analysis. Plasmodium vivax miR-451, miR-16 ↓ Chamnanchanunt and colleagues [248] miR-7977 ↑ Kaur and colleagues [249]…”
Section: Mirnas In Sepsismentioning
confidence: 99%
“…Still, some issues remain, including the lack of a standardized protocol regarding specimen collection, handling, and analysis. Plasmodium vivax miR-451, miR-16 ↓ Chamnanchanunt and colleagues [248] miR-7977 ↑ Kaur and colleagues [249]…”
Section: Mirnas In Sepsismentioning
confidence: 99%
“…The hsa-miR-15b-5p and hsa-miR-150-5p were up-regulated in the plasma-derived EVs from P. vivaxinfected patients but not in the P. falciparum-infected patients. An analysis of miRNAs from whole blood of adult imported falciparum malaria showed a down regulation of hsa-miR-150-5p [48]. Kaur et al have identi ed a potential biomarker for differential diagnosis between uncomplicated and complicated P. vivax malaria infection, hsa-miR-7977.…”
Section: Discussionmentioning
confidence: 99%
“…Kaur et al have identi ed a potential biomarker for differential diagnosis between uncomplicated and complicated P. vivax malaria infection, hsa-miR-7977. In addition, an increase in this miRNA was predicted to be involved in malaria pathogenesis through the transforming growth factor beta (TGF-β) signaling pathway [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for these characteristics, the successful entrepreneurship requires several experimental stages, from basic research towards final clinical validations. Initial steps for biomarker selection can be pursued using bioinformatic strategies, with large databases of the -omics providing valid alternatives [45,46]. Genome-wide translation dynamics studies as revealed by RP, and in contrast to transcriptomic approaches, offer a precise approximation for the P. falciparum proteome [8].…”
Section: Discussionmentioning
confidence: 99%